Skin Permeation and Cutaneous Hypersensitivity As a Basis for Making Risk Assessments of Chromium As a Soil Contaminant - Bagdon, Robert E.; Hazen, Robert E. (Environmental health perspectives, 1991)
A literature review of experimental and human exposure studies of skin permeation and cutaneous hypersensitivity reactions evoked by chromium was carried out to provide a basis for making a risk assessment of chromium as a soil contaminant. In vitro and in vivo studies demonstrated that 1 to 4% of the applied dose of hexavalent and trivalent chromium to guinea pig skin penetrated skin within 5 to 24 hours after application. Ultrastructural investigations showed that hexavalent chromium localized intracellularly and extracellularly in the upper layers of guinea pig epidermis. The potential of hexavalent chromium to produce a skin sensitization reaction is readily demonstrated using animal models. The incidence and characteristics of chromium-induced skin hypersensitivity as a clinical entity are described. A health effects survey of populations exposed to chromium slag in soil in Tokyo, Japan extending over 8 years indicated a tendency toward symptoms characterized as headache, chromic fatigue, and gastrointestinal complaints, positive occult blood tests, minute hematuria and albuminuria suggestive of incipient renal disease, and a tendency toward an increase in contact dermatitis that was seasonally related. Based on these data, the cleanup level of total chromium in soil is designated as 75 mg/kg. It is proposed that levels of total chromium lower than 75 mg/kg in soil would avoid undue risk of contact dermatitis.